FIGURATIVE LANGUAGE AND ITS MEANING ON ED SHEERAN’S SONG LYRICS - Darwin Fajar; I Made Netra; Ni Luh Sutjiati Beratha (Universitas Warmadewa, 2024)
This study is aimed to identify the figurative language and to analyze the meaning found on Ed Sheeran’s Song Lyrics. The data sources were four Ed Sheeran’s songs namely Photograph, Thinking Out Loud, Afire Love, and Dive taken from YouTube for the audios and a website called genius.com for the lyrics. The data were collected through documentation method and note-taking technique. Descriptive-qualitative method was applied to analyze the data using theory of figurative language by Knickerbocker and Reninger and theory of meaning by Leech. The result of the study shows that there are 6 kinds of figurative language found, namely simile, metaphor, personification, synecdoche, hyperbole, and irony. The lyrics containing figurative expression show implied meanings that can be classified into connotative and affective. The meanings found are about love, sadness, and awareness of each other.